Preparation method of nano-porous Cu6Sn5 type high-entropy intermetallic compound and application of nano-porous Cu6Sn5 type high-entropy intermetallic compound in electrocatalytic ammonia production

By preparing nanoporous Cu6Sn5 type high-entropy intermetallic compounds, the problem of difficulty in preparing high-entropy intermetallic compounds in the prior art is solved, efficient preparation under mild conditions is achieved, and its catalytic activity and ammonia production selectivity in electrocatalytic applications are improved.

CN119663090APending Publication Date: 2025-03-21HUNAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411865653.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to prepare high entropy intermetallic compounds, especially non-precious metals, under mild conditions, and there are problems of catalytic activity and reaction site exposure in electrocatalytic applications.

Method used

By preparing nanoporous Cu6Sn5 high-entropy intermetallic compounds, the master alloy preparation and selective corrosion methods are used, including chemical corrosion and electrochemical corrosion, and the Sn atomic ratio and corrosion conditions are regulated to form materials with high-entropy alloy characteristics.

Benefits of technology

The nanoporous Cu6Sn5 type high-entropy intermetallic compounds are efficiently prepared under mild conditions, which improves their intrinsic catalytic activity and ammonia production selectivity and charge utilization efficiency of electrocatalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663090A_ABST
    Figure CN119663090A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a nano-porous Cu6Sn5 type high-entropy intermetallic compound and application of the nano-porous Cu6Sn5 type high-entropy intermetallic compound in electro-catalytic ammonia production. The high-entropy catalytic material can be obtained through metal melting and selective corrosion; active sites can be regulated and controlled through component regulation and control, the obtained material has the structural characteristics of short-range disorder in unit cells and long-range order above unit cells, and creation of various types of functional materials is met. The high-entropy intermetallic compound material provided by the invention is simple and convenient to prepare, shows excellent ammonia production selectivity and charge utilization efficiency in an electro-catalysis nitrate reduction reaction, and lays a solid foundation for development of novel metal materials and electro-catalysis application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nanoporous Cu6Sn5 type high entropy intermetallic compound material, a preparation method and an application thereof in electrocatalytic ammonia production, and belongs to the field of electrocatalytic functional materials. Background Art

[0002] In recent years, with the continuous advancement of material science exploration, new metal functional materials have developed rapidly. Highly ordered atomic array structures represented by intermetallic compounds and multi-component mixed cell structures represented by high-entropy alloys have received a lot of research attention, providing research opportunities for the development of high-performance structural and functional materials, and have broad application prospects in the fields of water electrolysis and carbon dioxide reduction. High-entropy intermetallic compounds have a special structure with ordered atomic arrays and multi-component mixed entropy effects, forming a long-range cell structure with ordered structure and short-range atomic arrangement disorder, providing a new opportunity for the development of new materials.

[0003] As the research on high-entropy intermetallic compounds is on the rise, there is an urgent need to expand the types of materials, develop reliable preparation methods, and explore effective functional applications. The difficulty in preparing such materials is that multiple metal elements are prone to form binary or ternary intermetallic compounds during the alloying process, but it is difficult to form quaternary or even quinary intermetallic compounds. In current research, people use metal salt reduction (CN202310094201.1, CN202211033742.5, CN202211560956.8, CN202211033742.5, CN202210187460.4), metal smelting and sintering (CN202210463124.8), high-energy ball milling and ion cladding (CN202310530754.7, CN202210690438.1, CN202111079376.2) and other methods to obtain multinary metal compounds that meet specific functional applications. However, the preparation of high-entropy metal compounds under milder conditions, especially high-entropy metal compounds that do not contain precious metals, is still a major challenge. At the same time, in order to meet the needs of efficient chemical, electrochemical and other catalytic conversion applications, it is worth exploring in depth to develop universal methods for preparing high-entropy intermetallic compound materials, design appropriate material components to improve their intrinsic catalytic activity, and construct rich micro-nano structures to increase the exposure of active sites in materials.

[0004] Therefore, exploring the preparation methods of non-precious metal high-entropy intermetallic compound materials and their catalytic applications has important scientific significance and application value. Summary of the invention

[0005] In response to the preparation and application requirements of high entropy intermetallic compound materials, the present invention discloses a preparation method of a nanoporous Cu6Sn5 type high entropy intermetallic compound and its application in electrocatalytic nitrate reduction to produce ammonia.

[0006] The present invention is achieved through the following technical solutions:

[0007] A nanoporous Cu6Sn5 type high entropy intermetallic compound material, characterized in that the components are (Cu x M y )6Sn5, wherein M contains at least three elements of Ni, Co, Fe, Cr, and Mn, x≥y, and the atomic ratios of the elements in M ​​are equal or nearly equal.

[0008] Furthermore, a nanoporous Cu6Sn5 type high entropy intermetallic compound material is provided, characterized in that the value of x / y is preferably 1-2.

[0009] A nanoporous Cu6Sn5 type high entropy intermetallic compound material, characterized in that its preparation method comprises the following steps:

[0010] (1) Preparation of master alloy: The constituent metals are melted into a uniform alloy ingot according to a specific atomic ratio, the surface oxide film is polished to remove the ingot, and the master alloy strip is obtained by melting and spinning;

[0011] (2) Selective corrosion: The obtained master alloy strip is chemically or electrochemically corroded in an acidic solution, and the reaction time is controlled to obtain a nanoporous Cu6Sn5 type high entropy intermetallic compound.

[0012] Furthermore, in step (1), the Sn atomic ratio is 70%-94%, preferably 80%.

[0013] Furthermore, in step (1), the belt spinning speed is 2-5k rpm, preferably 3k rpm.

[0014] The selective corrosion method includes the following two methods:

[0015] (1) Chemical corrosion method: The master alloy strip is placed in a sufficient amount of dilute nitric acid solution to react, and the active Sn phase in the master alloy strip is removed by corrosion reaction to form a Cu6Sn5 type high entropy metal compound with a nanoporous structure.

[0016] Furthermore, the concentration of the nitric acid solution in the chemical etching is preferably 0.5M.

[0017] Furthermore, the chemical etching reaction time is 10-16 hours, preferably 12 hours.

[0018] (2) Electrochemical corrosion method: Using a sufficient amount of dilute hydrochloric acid solution as the electrolyte, the active Sn phase in the master alloy strip is corroded by the three-electrode electrochemical constant voltage method to form a Cu6Sn5 type high entropy intermetallic compound with a nanoporous structure.

[0019] Furthermore, the concentration of the hydrochloric acid solution in the electrochemical corrosion is preferably 0.5M.

[0020] Furthermore, the electrochemical corrosion potential is preferably -0.30 V vs Ag / AgCl, and the reaction time is 1-2 hours.

[0021] The nanoporous Cu6Sn5 type high entropy intermetallic compound material is used for the electrocatalytic nitrate reduction reaction to produce ammonia.

[0022] Furthermore, the nanoporous material is used as a catalytically active material in the application of electrocatalytic nitrate reduction to produce ammonia, the concentration of nitrate in the electrolyte is 0.01-1M, and the reduction potential ranges from -0.1 to -0.5V vs RHE.

[0023] Since the atomic radius of metals such as Ni, Co, Fe, Cr, and Mn is close to that of Cu, one or more of these atoms can enter the Cu6Sn5 lattice and randomly replace the position of Cu atoms. x M y )6Sn5, x ≥ y can keep the lattice structure of the obtained material as Cu6Sn5 type, and the substitution of Cu position increases the configuration entropy of the system, thus forming a series of medium entropy and high entropy intermetallic compounds. 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 material, Ni, Co, and Fe atoms replace the Cu atom, but the material still appears as Cu6Sn5 phase. This composition can play multiple roles in Cu adsorption and activation of nitrate, Ni, Co, and Fe in generating active hydrogen and promoting hydrogenation reaction, and Sn in inhibiting hydrogen evolution. When the value of x / y is preferably 1-2, each metal element in the obtained material can show a multi-component synergistic effect, which is beneficial to their respective characteristics, realize the catalytic process of atomic coordination, and is beneficial to multi-step conversion reactions. When the value of x / y is preferably 1, the five-element alloy (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 The configurational entropy of )6Sn5 is 1.54R, which exceeds the entropy limit of high entropy alloys (1.5R, R is the gas constant). Therefore, by regulating the type and ratio of the substitution components, a series of high entropy intermetallic compounds can be obtained.

[0024] Due to the difference in reaction activity, the metal Sn phase dissolves before the intermetallic compound phase during chemical and electrochemical corrosion. By designing a master alloy with an excess of Sn components and selectively corroding the active Sn phase, an intermetallic compound with a nanoporous structure can be obtained, which provides favorable conditions for the preparation of a large number of new materials. Under ideal dealloying conditions, 70-94% of Sn atoms correspond to 45-89% porosity; considering the specific surface area requirements of electrocatalytic applications, 80% of Sn atoms are preferred, corresponding to a porosity of 63.3%; within the speed range of 2k-5k rpm, the alloy solution quickly cools and crystallizes to form an intermetallic compound phase and an excess Sn metal phase, which is conducive to the formation of a continuous porous structure in the subsequent corrosion process; considering the uniformity of microphase crystallization, 3krpm is preferred.

[0025] Since the activity of Sn metal phase is higher than that of intermetallic compound phase, it can be removed by chemical corrosion or electrochemical corrosion under acidic conditions. In chemical corrosion, a dilute strong acid solution can be used to corrode Sn(2H + +Sn=H2↑+Sn 2+ ). The master alloy strip is placed in a sufficient amount of 0.5M dilute nitric acid solution, and depending on the amount of the reactants, a stable target phase can be obtained by reacting for 10-16 hours, preferably 12 hours. In the electrochemical corrosion, a dilute strong acid solution is used as the electrolyte, the master alloy strip is used as the working electrode, Ag / AgCl (saturated KCl) is used as the reference electrode, and a carbon rod is used as the counter electrode. A potential of -0.50V vs Ag / AgCl or above is applied to corrode Sn (Sn-2e - =Sn 2+ ). According to the requirements of moderate reaction speed and selective corrosion, a sufficient amount of 0.5M dilute hydrochloric acid solution is preferably used as the electrolyte, and the preferred corrosion potential is -0.30V vs Ag / AgCl; according to the different scales of the master alloy strips, the reaction time is 1-2 hours.

[0026] The preparation method of the nanoporous high entropy intermetallic compound material is simple, fast, and suitable for mass production processes; the obtained material has the multi-component characteristics of high entropy alloys, forming short-range disordered atomic substitution in the unit cell; at the same time, it has the lattice order characteristics of intermetallic compounds, forming a long-range ordered multi-principal unit cell arrangement above the unit cell. That is, the active site regulation can be achieved through component regulation, and the obtained material has the structural characteristics of short-range disorder in the unit cell and long-range order above the unit cell, which meets the creation of various types of functional materials. This is a feature that traditional pure high entropy alloys and pure intermetallic compounds do not have. The method disclosed in this patent directly obtains nanoporous Cu6Sn5 type high entropy intermetallic compound materials, which is creative and novel.

[0027] Nitrate (NO3 -) is widely present in industrial wastewater and domestic sewage, and its enrichment will cause serious harm to ecological safety and human health. Therefore, effective removal of NO3 - To reduce NO3 in water - Electrocatalytic nitrate reduction to ammonia is a feasible way to eliminate nitrate pollution (NO3 - -8e - +6H2O=NH3+9OH - ), and its ammonia product can be used as nitrogen fertilizer, refrigerant and hydrogen energy carrier after separation (Energy Environ. Sci. 2024, 17, 8787-8800; J. Colloid Interface Sci. 2024, 676, 323-330.). Therefore, the selective production of ammonia by electrocatalytic nitrate reduction reaction is a "kill two birds with one stone" green strategy, which is effective in removing NO3 in wastewater. - , and provides a feasible way to prepare value-added ammonia products, and thus has attracted much attention (Adv. Mater. 2024, 36, 2304021.). In order to improve the activity and product selectivity of the electrocatalytic reaction, develop efficient and low-cost electrocatalytic materials, and enhance the NO3 - The conversion kinetics, inhibition of hydrogen evolution side reactions, and in-depth understanding of the electrocatalytic reaction mechanism are hot topics in cutting-edge research. In recent years, alloy materials represented by Cu have shown excellent catalytic performance in nitrate reduction reactions, but Cu metal is not easy to catalyze the production of active hydrogen (H*) intermediates, resulting in toxic reduction products NO2 - Alloying is a feasible way to develop excellent catalytic materials, but the use of CuSn-based high entropy intermetallic compounds for electrocatalytic nitrate reduction to produce ammonia has not been reported. The present invention develops a new type of catalytic material, which is creative and practical.

[0028] Before testing the electrocatalytic nitrate reduction reaction of the material to produce ammonia, a sample is first taken to make a catalytic electrode. The nanoporous high entropy intermetallic compound material is weighed and dispersed in an ethanol solution, a Nafion dispersion is added as a stabilizer, and the dispersion is coated on carbon paper. The carbon paper electrode coated with the catalytic material is used as the working electrode, a 1M KOH solution containing a specified concentration of KNO3 is used as the electrolyte, a Hg / HgO electrode is used as the reference electrode, and a platinum sheet is used as the counter electrode. An appropriate potential is applied to carry out the electrocatalytic nitrate reduction reaction to produce ammonia. The amount of ammonia is determined by the indophenol blue color development method, and the ammonia production rate (YR) and Faraday efficiency (FE) are calculated to evaluate the catalytic activity and reaction adaptability of the material to produce ammonia. Preferably, the concentration of nitrate in the electrolyte is 0.01-1M, and the reduction potential ranges from -0.1 to -0.5V vs RHE.

[0029] In summary, during the material preparation process, the Sn removal reaction provides the driving force for the ordered rearrangement of atoms, and the multi-metal element substitution effectively regulates the metal-metal interaction and local electronic structure. At the same time, the synergistic effect of multiple components promotes nitrate activation, active hydrogen generation and hydrogenation conversion, thereby improving the intrinsic catalytic activity; the dealloying process forms a rich nanoporous structure, exposing a rich electrocatalytic reaction active site. Therefore, the material provides an excellent catalyst for the electrocatalytic nitrate reduction to ammonia reaction. Furthermore, the electrocatalytic nitrate reduction reaction experiment shows that the nanoporous Cu6Sn5 type high entropy metal compound exhibits excellent ammonia production selectivity and charge utilization efficiency, reflecting the practicality of this patent. Therefore, the preparation of the nanoporous Cu6Sn5 type high entropy metal compound disclosed in this patent and its application in electrocatalytic nitrate reduction to ammonia production have significant creativity and practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Cu5Ni5Fe5Co5Sn 80 XRD pattern of master alloy strip;

[0031] Figure 2 Chemical corrosion (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 ) XRD patterns of Cu6Sn5 high entropy intermetallic compound and Cu6Sn5 intermetallic compound;

[0032] Figure 3 Chemical corrosion (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )SEM image of 6Sn5 high entropy intermetallic compound;

[0033] Figure 4 Chemical corrosion (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )EDS image of 6Sn5 high entropy intermetallic compound;

[0034] Figure 5 It is electrochemical corrosion (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )XRD pattern of 6Sn5 high entropy intermetallic compound;

[0035] Figure 6 It is electrochemical corrosion (Cu 0.25 Ni 0.25 Fe 0.25 Co0.25 )SEM image of 6Sn5 high entropy intermetallic compound;

[0036] Figure 7 It is electrochemical corrosion (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )EDS image of 6Sn5 high entropy intermetallic compound;

[0037] Figure 8 It is electrochemical corrosion (Cu 0.50 Ni 0.25 Fe 0.25 )6Sn5 and (Cu 0.50 Ni 0.25 Co 0.25 )XRD pattern of 6Sn5 intermetallic compound;

[0038] Fig. 9 After electrochemical corrosion (Cu 0.50 Ni 0.25 Fe 0.25 )6Sn5(a) and (Cu 0.50 Ni 0.25 Co 0.25 )6Sn5(b) SEM image of intermetallic compound;

[0039] Fig.10 Yes (Cu 0.25 Ni 0.25 Fe 0.25 Mn 0.25 )6Sn5 and (Cu 0.25 Ni 0.25 Fe 0.25 Cr 0.25 )XRD pattern of 6Sn5 high entropy intermetallic compound;

[0040] Fig.11 Cu4Ni4Fe4Cr4Co4Sn 80 XRD pattern of master alloy strip;

[0041] Fig.12 Chemical corrosion (Cu 0.25 Ni 0.25 Fe 0.25 Cr 0.20 Co 0.25 )XRD pattern of 6Sn5 high entropy intermetallic compound;

[0042] Fig.13 Cu5Ni5Pd5Co5Sn 80 XRD pattern of master alloy strip;

[0043] Fig.14 Chemical corrosion (Cu 0.25 Ni 0.25 Pd 0.25 Co 0.25 )XRD pattern of Sn4 high entropy intermetallic compound;

[0044] Fig.15 Yes (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 ) Ammonia production rate (YR, dotted line graph) and Faraday efficiency (FE, bar graph) of 6Sn5 material electrocatalytic nitrate reduction;

[0045] Fig.16 Yes (Cu 0.50 Ni 0.25 Fe 0.25 )6Sn5(1),(Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5(2) and (Cu 0.50 Ni 0.25 Co 0.25 ) Ammonia production rate (YR, diagonal bar graph) and Faraday efficiency (FE, bar graph) of electrocatalytic nitrate reduction of 6Sn5(3) material;

[0046] Fig.17 Yes (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )The ammonia production rate (YR, diagonal bar graph) and Faraday efficiency (FE, bar graph) of 6Sn5 material electrocatalyzed reduction of KNO3 at different concentrations to produce ammonia. Specific embodiments

[0047] In order to make the purpose, preparation and application technical solutions of the present invention clearer, the following is a detailed description with reference to the embodiments.

[0048] Example 1 Nanoporous (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 High Entropy Intermetallic Compound Prepared by Chemical Etching

[0049] According to Cu5Ni5Fe5Co5Sn 80The atomic ratio of high purity Cu, Ni, Fe, Co, Sn was molten in an electric arc furnace to obtain a master alloy ingot; the master alloy strip was spun at a speed of 3k rpm in a strip spinning machine. The obtained strip was chemically etched in a sufficient amount of 0.5M nitric acid solution for 12 hours, and the remaining precipitate was separated, washed, and dried to obtain a black powder. 20 Sn 80 The high purity Cu and Sn are melted in an electric arc furnace to obtain a master alloy ingot; the master alloy strip is spun at a speed of 3k rpm in a strip spinning machine. The obtained strip is chemically etched in a sufficient amount of 0.5M nitric acid solution for 12 hours, and the remaining precipitate is separated, washed and dried to obtain a black powder.

[0050] XRD test shows that Cu5Ni5Fe5Co5Sn 80 The main phase of the master alloy strip is the metal Sn phase (such as the attached Figure 1 As shown), the alloy components are dispersed in the Sn matrix; after corrosion, a Cu6Sn5 intermetallic compound with the same crystal form is formed (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 high entropy alloy (such as attached Figure 2 SEM test shows that the obtained material presents a nanoporous structure formed by the accumulation of nanoparticles (as shown in the attached Figure 3 EDS test shows that the element ratio is consistent with the expected (see attached Figure 4 The above results show that the chemical etching method successfully prepared nanoporous (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )The successful preparation of 6Sn5 high entropy intermetallic compound.

[0051] Example 2 Nanoporous (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 High Entropy Intermetallic Compound Prepared by Electrochemical Corrosion

[0052] According to Cu5Ni5Fe5Co5Sn 80The high-purity Cu, Ni, Fe, Co, and Sn were melted in an arc furnace to obtain a master alloy ingot according to the atomic ratio; the master alloy strip was spun at a rate of 3k rpm in a strip spinning machine. A three-electrode system was constructed, with the master alloy strip as the working electrode, Ag / AgCl (saturated KCl) as the reference electrode, and a carbon rod as the counter electrode. Electrochemical corrosion was performed in a 0.5M hydrochloric acid solution at a constant potential of -0.30V vs Ag / AgCl until the corrosion current was close to zero. The etched strips were collected, washed, and dried to obtain black powder.

[0053] XRD test shows that after electrochemical corrosion, the Cu6Sn5 intermetallic compound crystal (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 high entropy alloy (such as attached Figure 5 SEM test shows that the obtained material has a nanoporous structure (as shown in the attached Figure 6 EDS test shows that the element ratio is consistent with the expected (see attached Figure 7 The above results show that the electrochemical corrosion method successfully prepared nanoporous (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 high entropy intermetallic compound. As a control, Cu component replaces Fe or Co, and Cu 10 Ni5Fe5Sn 80 and Cu 10 Ni5Co5Sn 80 The master alloy was electrochemically corroded. XRD test showed that after electrochemical corrosion, Cu6Sn5 intermetallic compound crystal structure (Cu 0.50 Ni 0.25 Fe 0.25 )6Sn5 and (Cu 0.50 Ni 0.25 Co 0.25 )6Sn5 quaternary metal compound (such as attached Figure 8 SEM test shows that the obtained material has a nanoporous structure (as shown in the attached Fig. 9 By replacing Co in the master alloy with Mn or Cr, a Cu6Sn5 intermetallic compound crystal structure (Cu 0.25 Ni 0.25 Fe 0.25 Mn 0.25 )6Sn5 and (Cu 0.25 Ni 0.25 Fe 0.25 Mn 0.25 )6Sn5 high entropy alloy (such as attached Fig.10 The results show that the method has a certain degree of universality. The product can be obtained by changing the speed of the master alloy within the range of 1k-5k rpm.

[0054] Example 3 Nanoporous (Cu 0.20 Ni 0.20 Fe 0.20 Cr 0.20 Co 0.20 )6Sn5 High Entropy Intermetallic Compound Prepared by Chemical Etching

[0055] According to Cu4Ni4Fe4Cr4Co4Sn 80 The pure metal is smelted into a uniform alloy ingot according to the atomic ratio, the surface oxide film is polished off, and the mother alloy strip is obtained by melting and spinning; the obtained strip is chemically corroded in a sufficient amount of 0.5M nitric acid solution for 12 hours, the remaining precipitate is separated, washed and dried to obtain a black powder.

[0056] XRD test shows that Cu4Ni4Fe4Cr4Co4Sn 80 The main phase of the master alloy strip is the metal Sn phase, and the alloy components are dispersed in the Sn matrix (such as the attached Fig.11 After corrosion, a Cu6Sn5 intermetallic compound crystal structure is formed (Cu 0.25 Ni 0.25 Fe 0.25 Cr 0.20 Co 0.25 )6Sn5 high entropy alloy (such as attached Fig.12 The above results demonstrate the successful preparation of hexameric nanoporous high-entropy intermetallic compounds.

[0057] Example 4 Nanoporous (Cu 0.25 Ni 0.25 Pd 0.25 Co 0.25 )6Sn5 High Entropy Intermetallic Compound Prepared by Chemical Etching

[0058] According to Cu5Ni5Pd5Co5Sn 80 The master alloy ingot is melted in an electric arc furnace with a high purity Cu, Ni, Pd, Co and Sn in an atomic ratio of 1.50 μm. The master alloy strip is spun at a speed of 3 k rpm in a strip spinning machine. The obtained strip is chemically etched in a sufficient amount of 0.5 M nitric acid solution for 12 hours, and the remaining precipitate is separated, washed and dried to obtain a black powder.

[0059] XRD test shows that Cu5Ni5Pd5Co5Sn 80 The main phases of the master alloy strip are PdSn4 intermetallic compound phase and metal Sn phase (such as the attached Fig.13As shown), the alloy components are dispersed in the Sn matrix; after corrosion, a PdSn4 intermetallic compound crystal (Cu 0.25 Ni 0.25 Pd 0.25 Co 0.25 )Sn4 high entropy alloy (such as attached Fig.14 The above results show that the composition of the master alloy has a direct impact on the formation of nanoporous high-entropy intermetallic compounds. The atoms with a radius close to that of Cu atoms are mainly selected to replace the Cu sites of the Cu6Sn5 lattice, while the Pd atoms have a larger radius and play a leading role in supporting the lattice, making the obtained material a PdSn4 phase.

[0060] Example 5 Nanoporous (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 high entropy intermetallic compound electrocatalyzed nitrate reduction to ammonia

[0061] Weigh 5 mg of nanoporous (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 high entropy metal intermetallic compound material was prepared into 470 μL of ethanol dispersion, 30 μL of Nafion dispersion was added, and the dispersion was taken at 0.5 mg cm -2 The carbon paper electrode coated with the catalytic material was used as the working electrode, 1M KOH electrolyte containing 0.1M KNO3, Hg / HgO electrode as the reference electrode, and platinum sheet as the counter electrode, and different potentials were applied to carry out the nitrate reduction reaction to produce ammonia.

[0062] The amount of ammonia was determined by the indophenol blue colorimetric method, and the ammonia production rate (YR) and the Faradaic efficiency (FE) were calculated (see Appendix). Fig.14 At the optimal potential, the ammonia production rate reached 14.13 mg h -1 mg cat -1 , the Faraday efficiency reached 98.71%, indicating that the material has significant electrocatalytic activity in nitrate reduction to ammonia. 0.50 Ni 0.25 Fe 0.25 )6Sn 5、 (Cu 0.50 Ni 0.25 Co 0.25 )6Sn5 also has electrocatalytic activity in nitrate reduction reaction, but (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25)6Sn5 material shows the best performance (such as attached Fig.15 shown).

[0063] Example 6 Nanoporous (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 high entropy intermetallic compound electrocatalyzed nitrate reduction to ammonia

[0064] Weigh 5 mg of nanoporous (Cu 0.25 Ni 0.25 Fe 0.25 Co 0.25 )6Sn5 high entropy metal intermetallic compound material was prepared into 470 μL of ethanol dispersion, 30 μL of Nafion dispersion was added, and the dispersion was taken at 0.5 mg cm -2 The carbon paper electrode coated with the catalytic material was used as the working electrode, a 1M KOH solution containing 10-1000mM KNO3 was used as the electrolyte, a Hg / HgO electrode was used as the reference electrode, and a platinum sheet was used as the counter electrode. A potential of -0.30V vs RHE was applied to carry out the nitrate reduction reaction to produce ammonia.

[0065] The amount of ammonia was determined by the indophenol blue colorimetric method, and the ammonia production rate (YR) and the Faradaic efficiency (FE) were calculated (see Appendix). Fig.16 The material exhibits outstanding ammonia production activity and Faradaic efficiency in a wide range of substrate concentrations, indicating that the material is adaptable to the electrocatalytic nitrate reduction reaction to produce ammonia.

[0066] In summary, the present invention relates to a method for preparing a nanoporous Cu6Sn5 type high entropy intermetallic compound and its application in electrocatalytic ammonia production. The application scenarios and embodiments described above are not intended to limit the present invention. Any person skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention is defined by the scope of the claims.

Claims

1. A nanoporous Cu6Sn5 type high entropy intermetallic compound material, characterized in that: The components are (Cu x M y )6Sn5, wherein M contains at least three elements of Ni, Co, Fe, Cr, and Mn, x≥y, and the atomic ratios of the elements in M ​​are equal or nearly equal.

2. A nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 1, characterized in that: The value of x / y is preferably 1-2.

3. The nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 1, characterized in that: The material preparation method comprises the following steps: (1) Preparation of master alloy: The constituent metals are melted into a uniform alloy ingot according to a specific atomic ratio, the surface oxide film is polished to remove the ingot, and the master alloy strip is obtained by melting and spinning; (2) Selective corrosion: The obtained master alloy strip is chemically or electrochemically corroded in an acidic solution, and the reaction time is controlled to obtain a nanoporous Cu6Sn5 type high entropy intermetallic compound.

4. The nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 3, characterized in that: In the preparation of the master alloy, the Sn atomic ratio is 70%-94%, preferably 80%.

5. The nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 3, characterized in that: During the preparation of the master alloy, the belt spinning speed is 2-5k rpm, preferably 3k rpm.

6. The nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 3, characterized in that: Selective corrosion includes the following two methods: (1) Chemical corrosion method: The master alloy strip is placed in a sufficient amount of dilute nitric acid solution to react, and the active Sn phase in the master alloy strip is removed by corrosion reaction to form a Cu6Sn5 type high entropy metal compound with a nanoporous structure. (2) Electrochemical corrosion method: Using a sufficient amount of dilute hydrochloric acid solution as the electrolyte, the active Sn phase in the master alloy strip is corroded by the three-electrode electrochemical constant voltage method to form a Cu6Sn5 type high entropy metal compound with a nanoporous structure.

7. The nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 6, characterized in that: The concentration of the nitric acid solution in the chemical corrosion is preferably 0.5M; the corrosion reaction time is 10-16 hours, preferably 12 hours.

8. The nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 6, characterized in that: The concentration of the hydrochloric acid solution in the electrochemical corrosion is preferably 0.5 M, the corrosion potential is preferably -0.30 V vs Ag / AgCl, and the reaction time is 1-2 hours.

9. The nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 1, characterized in that: The material is applied to the electrocatalytic nitrate reduction reaction to produce ammonia.

10. The nanoporous Cu6Sn5 type high entropy intermetallic compound material according to claim 9, characterized in that: In the application of electrocatalytic nitrate reduction to produce ammonia, the concentration of nitrate in the electrolyte is 0.01-1M, and the reduction potential ranges from -0.1 to -0.5V vs RHE.

Citation Information

Patent Citations

  • High-entropy intermetallic compound with characteristics of high strength and wide-temperature-range wear resistance

    CN113774265A

  • A structurally ordered high-entropy intermetallic compound, its preparation method and application as a fuel cell cathode catalyst

    CN114566662B

  • A high-entropy intermetallic compound material, its preparation method, and electronic solder.

    CN114799616B

  • Novel flexible graded nano-porous high-entropy alloy and preparation method thereof

    CN115094414A

  • Supported high-entropy intermetallic compound catalyst, preparation method and application

    CN115360367A